Interaction between double nonspherical bubbles in compressible liquid under the coupling effect of ultrasound and electrostatic field - Deng Jin-Jie; Yu Ming; Yang Ri-Fu (Acta Acustica, 2022)
A dynamic model for a double-bubble system in compressible liquid under the coupling effect of ultrasound and electrostatic field was developed here. In this study, we mainly discussed the effect of the interaction on the investigated bubble using the numerical solutions to the theoretic model. The variable parameters are the distance between bubble centers and the initial radius of the adjacent bubble. In addition, we applied approximate equations to analyse variations of the internal gas pressure and temperature of a bubble. We found that, the oscillation amplitude of a bubble with an adjacent bubble significantly reduces, compared to that of an isolated bubble.